Against the rules - Suzanne, Jamie; Pascal, Francine (New York, New York A Bantam Skylark Book, 1987)
Elizabeth collaborates on a school play with her friend Sophia Rizzo, even though her parents tell her to stay away from Sophia, whose brother has been in reform school.
Keywords: Large type books; Friendship -- Fiction; Large type books